The Show and Tell or Deliver the Presentation strategies: which is effective more? - Occe Luciana (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2021)
In several non-English educational institutions in Indonesia, the problem of students who are not fluent in speaking English is still quite a lot. The various obstacles faced by each student are very diverse, and it will not be far from limited vocabulary mastery, self-confidence, and also weak self-motivation for the spirit of learning. Various methods are used to improve the ability to speak English. Some are compatible with one method, but not the other, and vice versa. This study aims to determine whether the method that STIE WIkara students admit is more effective for practicing speaking English, is the Show and Tell method or Presentation with power point. The results of the study show that STIE Wikara students admit that an effective method for practicing speaking English is a method that makes it easier for them to speak without thinking to translate into English.